Gauging the Media Discourse and the Roots of Islamophobia Awareness in Spain - Corral, Alfonso (Religions, 2023)
This article analyses the media discourse about Islamophobia in Spain. Specifically, an overview of all the appearances of the term in four Spanish newspapers (ABC, El Mundo, El País, and La Vanguardia) is provided with the aim of finding out when the term was first used and became standard language. The study also demonstrates the links with the public interest and identifies the ideological and terminological attitudes in the discourse of each newspaper. The corpus includes 1475 news articles since the first reference (in 1987) to the term Islamophobia and May 2022, which were quantitatively examined in two steps. While the first was manual and served to document the historical background, the second allowed us to monitor the media content by means of Sketch Engine. Furthermore, the searches for the term “islamofobia” in Google Trends from Spain were also reviewed. The main findings show that both terrorist attacks in Western countries and the controversies surrounding freedom of speech are key to the emergence and normalisation of the concept, particularly since 2015. However, the interest of each newspaper differs, with El País covering the topic most frequently. This left-wing newspaper offers some notable variations in terminology as well. While the three right-wing newspapers consistently relate Islamophobia to threat, the vocabulary used in El País underpins the victimisation of the Arab-Islamic population. According to the Sketch Engine analysis, the usual terms that occur in combination with Islamophobia are racism, terrorism, violence, hate, anti-semitism, and xenophobia. Finally, Google Trends data confirmed the peak in public interest in the Barcelona and Cambrils attacks (17A).